Animisme dan Dinamisme dalam Masyarakat Serta Kondisi Keislaman Indonesia Hari Ini Gerakan Studi Islam - Andre Meizandi (CV Kalimasada Group, 2025)
Primitive society believed that all things, both animate and inanimate, had a spirit. This understanding is called animism, as a primitive society they also have not been able to clearly distinguish between what should be called matter and what is called spirit. For them the spirit is composed of a very fine substance or matter, which is close to vapor or air. The spirit has strength and will, can feel happy and become angry. If he is angry he can endanger human life, therefore his pleasure must be sought. Those who know and are good at taking the hearts of these spirits are shamans or sorcerers as is the case with dynamism beliefs, in dynamism beliefs, various kinds of traditional ceremonies are performed to control the spirits inherent in an object so as not to disturb or even cause damage to people's lives. These supernatural objects (fetishes) are collected as a powerful weapon against the enemy, can be the cause of everything that benefits society. This then underlies the primitive society adheres to the beliefs of animism and dynamism. Even so, it shows that these beliefs give birth to values. Due to the tendency of tradition to maintain itself against possible changes in the value system, in reality traditional ties are often an obstacle to the development of civilization and human progress. Therefore, humans must leave all forms of traditional value systems, and embrace beliefs that are truly the truth. The absolute truth is God. Nevertheless, humans must still uphold the tolerance of other human beliefs, so that they become a pluralistic society.